Synthesis and applications of novel bisquinolizidine derivatives from bio renewable resources - Ferreira, Daniela Filipa Ribeiro (2023)
Tese de mestrado, Química Medicinal e Biofarmacêutica, 2023, Universidade de Lisboa, Faculdade de Farmácia.